Nano Silicagel Supported by Phosphoric Acid for Synthesis of Azoic Dyes Based on Naphthol - Mirjalili, Mohammad; Hedayat, Laleh (Asian Journal of Chemistry, 2010)
Synthesis of some azoic dyes based on a-naphthol requires special conditions such as low temperature, use of dense acids and high pressure. Aside from great expenses and difficulties in preparing conditions of solution, depreciation of dye-making devices due to the application of dense acids is regarded as another problem in this system. This paper tries to use a new method to remove these difficulties. Producing dyes using solid acids appears to be more effective than applying aqueous ones. One of the advantages of this system is the reduction of device corrosion, prevention of any damaging to the environment, an increase in efficiency and simplicity of the method. Applying this method, some azoic dyes based on a-naphthol, in room temperature and atmosphere pressure, were synthesized in high per cent and in a short time. The structure of the synthesized dye was investigated by FTIR. The synthesized dye was then used for dyeing some textile fibers in order to identify the best condition for dye absorbing and for studying the quality of these dyes on fabrics. Consequently, washing fastness test, staining test, light fastness were done. The results show that synthesized dyes are placed in acidic dyes category.